Pushing The Limits in Cardiac Surgery: Aortic Valve Replacement in Severe Aortic Regurgitation in Severely Dilated Left Ventricle with Moderate Left Ventricular Dysfunction - Joshi, Rheecha; Chaudhary , Jay Mangal; Acharya , Sampada; Nemkul, Urusha; Thapa, Esna; Devkota , Sachin; Upreti, Gaurav; Gautam, Navin (Journal of National Heart and Lung Society Nepal, 2025)
Left ventricular dysfunction is a major prognostic factor in aortic valve replacement (AVR) for aortic regurgitation (AR). Patients with reduced left ventricular ejection fraction(LVEF) with dilated left ventricle (LV) are high risk surgical candidate and are treated medically. However, surgery may offer survival benefits over medical therapy. We report a 25-year-old male with severe AR with repeated admission for NYHA class IV heart failure. Despite the severe LV dysfunction and dilation, the cardiac surgeons pushed the boundaries and the patient underwent aortic valve replacement (AVR) with a mechanical valve via median sternotomy. The procedure was uneventful with smooth recovery. On follow up patient had good LV reverse remodeling, improved LVEF and better quality of life.